Efficiency and Environmental Impacts of Electricity Restructuring on Coal-Fired Power Plants - H. Ron Chan; Harrison Fell; Ian A. Lange; Shanjun Li (Center for Economic Studies and ifo Institute (CESifo), 2013)
We investigate the impacts of electricity market restructuring on fuel efficiency, utilization and, new to this area, cost of coal purchases among coal-fired power plants using a panel data set from 1991 to 2005. Our study focuses exclusively on coal-fired power plants and uses panel data covering several years after implementation of restructuring. The estimation compares how investor-owned (IOs) plants in states with restructuring changed their behavior relative to IOs in states without. Our analysis finds that restructuring led to: (1) a two percent improvement in fuel efficiency for IOs, (2) a ten percent decrease in unit cost of heat input, and (3) a lower capacity factor even after adjusting for cross-plant generation re-allocation due to cost reductions. Based on these estimates, back-of-the-envelope calculations find that restructuring has led to about 6.5 million dollars in annual cost savings or nearly 12 percent of operating expenses and up to a 7.6 percent emissions reduction per plant.
Keywords: L50; Q40; Q50; 330; restructuring; efficiency; cost; utilization; emissions